Assessing the impact of green tourism on sustainable development: A case study of the United Arab Emirates - Khater, Maya; Chami, Yassine; Imad, Dina; Abouhaiba, Nagwa; Jaffal, Zeyad (Research Journal in Advanced Humanities, 2025)
Green tourism has become an important pillar of sustainable development due to its role in directing tourists to environmental tourism sites and mitigating environmental risks, while basically relying on protecting resources and reducing consumption. This study outlines the importance of this tourism in supporting sustainable development goals in the United Arab Emirates and harnessing tourism to implement development plans and evaluates the legal and policy frameworks that support its implementation. Using a descriptive and analytical methodology, the research explores legal and executive measures and initiatives taken by the UAE to apply green tourism in a manner that promises to contribute towards the promotion of a sustainable future and to enhance development at all levels. The findings reveal that the UAE has made significant progress in integrating green tourism into its overall sustainability agenda through policy interventions, infrastructure provision, and environmentally sustainable tourism policies. The UAE’s approach to green tourism serves as a model for other countries seeking to establish sustainable tourism sectors. However, challenges remain in achieving full synergy between tourism development and sustainability goals. The study emphasizes the importance of law enforcement, public-private partnerships, and continuous innovation to achieve green tourism as an important contribution to long-term environmental and economic sustainability.